Book review: Who cares about feeling good? The Who Cares? Trust. London, The Who Cares? Trust, 2008. 41pp, ISBN 1903239281 - Robyn Willis (Scottish Journal of Residential Child Care)
This is quite a small book with loads of pictures and it is also quite colourful. It’s not even like a book really because it looks like a set of big postcards that have been put together with a wire binder. It is written for kids in care and I thought it was quite good. It is about feeling good about yourself. It explains some things like 'self-esteem' and 'confidence' in an easy way. The other thing it does is that it talks about stress and bullying and self-harm. I know a lot of kids who get affected by things like that and I think a book like this could help them to see that they aren’t the only ones.